Development and Implementation of Curriculum Adaptation During The Covid-19 Pandemic - Muh Syauqi Malik; Sukiman Sukiman (Program Studi Pendidikan Agama Islam, 2021)
The outbreak of the Covid-19 pandemic has penetrated all people globally, including the Indonesian people who feel that the teaching and learning culture must follow health protocols. Still, the learning process must continue even though it is limited. This study aims to determine curriculum adaptation during the Covid-19 pandemic, teacher strategies, and its impact on MI Salafiyah Tajungsari and SDN Sitiluhur 02. This type of research used qualitative field studies with data sources for school principals, curriculum development teams, and teachers. Methods of data collection using observation, interviews, and documentation. Data analysis includes data reduction, data presentation, concluding, and verification. The technique of testing the validity of the data used triangulation of sources and methods. The research findings showed that MI Salafiyah Tajungsari uses an emergency curriculum with essential materials, while SDN Sitiluhur 02 uses a curriculum that simplifies critical competencies. The learning strategies used by teachers include online and offline. The difference lies offline. Offline at MI Salafiyah Tajungsari held limited face-to-face meetings, while offline at SDN Sitiluhur 02, students carried out the tasks assigned by the teacher and submitted their work to school. The impact of the adaptation curriculum has made the competency target of the school not maximally achieved.